Integrated transcriptomic and immune enzymatic analyses uncover coordinated immunometabolic responses in large yellow croaker (Larimichthys crocea) to Metanophrys sp. infection - Zhou, Ruiling; Sun, Kangshuai; Xie, Xiao; Yin, Fei; Galindo-Villegas, Jorge (Frontiers in Immunology, 2025)
Metanophrys sp. (Scuticociliatida) has recently emerged as a significant parasitic threat in large yellow croaker (Larimichthys crocea) aquaculture. To elucidate the host response, we conducted an experimental infection followed by an integrated analysis combining immune enzymatic profiling and transcriptome sequencing. Antioxidant and immune enzyme activities, including SOD, CAT, and MDA in the skin, gill, and liver, and LYZ and Na+/K+-ATPase in the skin and gill were monitored from 0 to 72 hours post-infection (hpi). The results revealed tissue- and time-specific significant changes, indicating increased oxidative stress and activation of compensatory antioxidant and mucosal immune defenses. At the resolution phase of infection (72 hpi), dorsal skin tissue was subjected to RNA sequencing (RNA-seq), identifying 6,360 differentially expressed genes (DEGs), including 3,164 upregulated and 2,702 downregulated transcripts. GO and KEGG enrichment analyses revealed strong activation of key immune signaling pathways, such as NOD-like receptor, IL-17, chemokine, and cytokine–cytokine receptor interaction, alongside metabolic reprogramming involving oxidative phosphorylation, glycolysis/gluconeogenesis, and lipid metabolism. Inflammatory mediators associated with IL-17 signaling, including cox2, cxcl8, mmp9 and hsp90, together with chemokine-related effectors such as akt, raf1, and rhoA were significantly upregulated, suggesting strong mucosal inflammation and thrombocyte involvement, functionally analogous to the platelet-activation pathway in mammals. Notably, immunometabolic convergence was evidenced by co-upregulation of genes such as il1b, il6, cxcl8, mmp9, pnpla2, and foxo1, reflecting the simultaneous activation of inflammatory and metabolic regulatory programs during host defense. Swiss-Prot annotations confirmed the conserved functional roles of these genes in cytokine signaling, energy mobilization, and tissue protection. qPCR validation of 12 representative genes showed strong concordance with the RNA-seq expression profile (R²=0.98). Together, these findings demonstrate that L. crocea mounts a temporally coordinated immunometabolic response to Metanophrys sp., providing mechanistic insights into mucosal defense and offering candidate biomarkers for targeted disease management in marine aquaculture.